2012
DOI: 10.1155/2012/576804
|View full text |Cite
|
Sign up to set email alerts
|

Cypermethrin-Induced Toxic Effect on Glycogen Metabolism in Estuarine Clam,Marcia Opima(Gmelin, 1791) of Ratnagiri Coast, Maharashtra

Abstract: Cypermethrin is a synthetic pyrethroid class of insecticide. Toxic effects of cypermethrin were studied by selecting Marcia opima as an animal model. Cypermethrins effect on the total glycogen content of mantle, gill, foot, hepatopancreas, male gonad and a female gonad of an estuarine clam, Marcia opima was examined. The clams were exposed to 1.58 ppm cypermethrin for acute and 1/10th of that concentration for chronic treatment. It was found that there was a decrease in glycogen content in various tissues as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…The decrease in the glycogen content of snail tissues after exposure to pollutant may be due to an increase in the glycogen degradation rate, 'glycogenolysis', 52 or to the greater utilization of glycogen for metabolic purposes and to combat toxic stress. 53 The obtained data are in line with Riaz et al 54 who showed that the glycogen contents were significantly decreased in fourth and sixth larval instars of two Pakistan populations of stored grain pest, Trogoderma granarium, exposed to LC 20 doses of emamectin, abamectin and spinosad alone and in various combinations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The decrease in the glycogen content of snail tissues after exposure to pollutant may be due to an increase in the glycogen degradation rate, 'glycogenolysis', 52 or to the greater utilization of glycogen for metabolic purposes and to combat toxic stress. 53 The obtained data are in line with Riaz et al 54 who showed that the glycogen contents were significantly decreased in fourth and sixth larval instars of two Pakistan populations of stored grain pest, Trogoderma granarium, exposed to LC 20 doses of emamectin, abamectin and spinosad alone and in various combinations.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, the glycogen content of EMB‐intoxicated snails was significantly lower than in untreated snails. The decrease in the glycogen content of snail tissues after exposure to pollutant may be due to an increase in the glycogen degradation rate, ‘glycogenolysis’, 52 or to the greater utilization of glycogen for metabolic purposes and to combat toxic stress 53 . The obtained data are in line with Riaz et al 54 .…”
Section: Discussionsupporting
confidence: 84%
“…Cypermethrin stress decreased total glycogen content in different organs/tissues of Marica opima and affected its metabolic activity (Tendulkar and Kulkarni, 2012). Oxidative stress produced by deltamethrin is one of the major mechanism of neurotoxicity (Romero et al, 2012).…”
Section: Hazardous Effects Of Pyrethroidsmentioning
confidence: 99%
“…They found depletion in carbohydrate level and suggested that naphthalene can induce hypoxic conditions, which result in the extra expenditure of carbohydrate metabolism. The decrease in glycogen content of the organisms exposed to pollutants was observed by several authors (Sarojini et al 1990;Mane and Kulkarni 1999;Mulet et al 2007;Moorthikumar and Muthulingam 2011;Tendulkar and Kulkarni 2012). The difference in glycogen energy budget observed between TA-E, TA-1 and TA-2 on the one hand and between TE-1 and TE-2 on the other hand shows that the amount of glycogen depleted was dose dependent.…”
Section: Changes In Energy Budgetsmentioning
confidence: 64%